High diversity of clinical Mycobacterium intracellulare in China revealed by whole genome sequencing - Song, Zexuan; Liu, Zhi; Ma, Aijing; Liu, Chunfa; He, Wencong; Zeng, Xiangjie; Wang, Yiting; He, Ping; Liu, Dongxin; Zhao, Bing; Xia, Hui; Wang, Shengfen; et al. (Frontiers in Public Health, 2022)
Mycobacterium intracellulare is the most common cause of nontuberculous mycobacterial lung disease, with a rapidly growing prevalence worldwide. In this study, we performed comparative genomic analysis and antimicrobial susceptibility characteristics analysis of 117 clinical M. intracellulare strains in China. Phylogenetic analysis showed that clinical M. intracellulare strains had high genetic diversity and were not related to the geographical area. Notably, most strains (76.07%, 89/117) belonged to Mycobacterium paraintracellulare (MP) and Mycobacterium indicus pranii (MIP) in the genome, and we named them MP-MIP strains. These MP-MIP strains may be regarded as a causative agent of chronic lung disease. Furthermore, our data demonstrated that clarithromycin, amikacin, and rifabutin showed strong antimicrobial activity against both M. intracellulare and MP-MIP strains in vitro. Our findings also showed that there was no clear correlation between the rrs, rrl, and DNA gyrase genes (gyrA and gyrB) and the aminoglycosides, macrolides, and moxifloxacin resistance, respectively. In conclusion, this study highlights the high diversity of M. intracellulare in the clinical setting and suggests paying great attention to the lung disease caused by MP-MIP.